2003
DOI: 10.1053/joca.2002.0871
|View full text |Cite
|
Sign up to set email alerts
|

Presence of pannus-like tissue on osteoarthritic cartilage and its histological character

Abstract: Pannus-like tissue exists in advanced OA cartilage, preferentially in the marginal zone. It expressed IL-1beta and MMP3, which strongly suggests that it contributes to cartilage degradation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
70
1
3

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(78 citation statements)
references
References 19 publications
4
70
1
3
Order By: Relevance
“…Pannus has been envisaged as a fibrovascular proliferative tissue that invades articular cartilage at the cartilage-synovium junction. Its formation has been considered to be characteristic of RA, but it has also been reported in OA, which may also be characterized by synovitis (21). It must also be pointed out that the pannus tissue evident microscopically in the present study is likely to differ substantially from the inflamed tissue associated with RA, in which florid destruction of articular cartilage has been documented.…”
Section: Discussionsupporting
confidence: 53%
“…Pannus has been envisaged as a fibrovascular proliferative tissue that invades articular cartilage at the cartilage-synovium junction. Its formation has been considered to be characteristic of RA, but it has also been reported in OA, which may also be characterized by synovitis (21). It must also be pointed out that the pannus tissue evident microscopically in the present study is likely to differ substantially from the inflamed tissue associated with RA, in which florid destruction of articular cartilage has been documented.…”
Section: Discussionsupporting
confidence: 53%
“…3). Although OA synovial tissue exhibits histological abnormalities as already reported (17), in the great majority of the cases, the histological changes in OA may be easily distinguished from those observed in RA. In contrast, histological abnormalities were absent in healthy synovium.…”
Section: Histological Analysis Of Clu Protein Expression In the Synoviumsupporting
confidence: 62%
“…Activated synovium can release proteases and cytokines which in turn accelerate the deterioration of adjacent cartilage lesions (22). Our study revealed a difference in LDH levels between the control group and the experimental osteoarthritis group.…”
Section: Discussionmentioning
confidence: 55%